Inexpensive methodology to prepare TiO2/CuInS2 hetero-junctions for photovoltaic applications - Di Iorio, Yesica Dolores (2017)
TiO2 and CuInS2 (CIS) hetero-junctions were prepared using low-cost, solution-based techniques. Using conducting glass (FTO) as substrate, a thin film of TiO2 and an ultrathin film of In2S3 that acts as buffer layer were deposited by spray pyrolysis. CIS was electrodeposited on top of this duplex layer, at pH 8, room temperature and at constant potential. A solar cell consisting of FTO/TiO2/In2S3/CIS/graphite was built in superstrate configuration. Morphology, thickness, crystalline structure and chemical composition were analyzed by electronic microscopy, x-ray diffraction and Raman spectroscopy. CuInS2 films were found to be crystalline with a thickness of 0.4 μm and showed good adhesion. Current-voltage curves in the dark and under illumination proved that the solution-based and vacuum-free deposition of these materials has promising photovoltaic applications. Different thicknesses of the buffer layer were evaluated and the best results were found for In2S3 layers deposited with 6 spray cycles. The best solar cell performance showed an efficiency equal to 3.3% with a Voc = 0.583 V, Jsc = 17.7 mA cm-2, FF = 0.32.